An 11-Year Agronomic, Economic, and Phosphorus Loss Potential Evaluation of Legacy Phosphorus Utilization in a Clay Loam Soil of the Lake Erie Basin - Zhang, Tiequan; Wang, Yutao; Tan, Chin S.; Welacky, Tom (Frontiers in Earth Science, 2020)
Legacy phosphorus (P) in agricultural soils has become a predominate source contributing to P loadings to Lake Erie since the mid-90s. The use of legacy P in soils can be an ultimate and effective way to mitigate the risk of agricultural P loss and to circumvent potential P rock reserve shortage, while sustaining crop production. A field experiment was conducted to assess the impacts of P draw-down (PDD) (i.e., use of legacy P in soils) on crop yields, P uptake and removal, and soil test P (Olsen P, an agronomic P calibration and environmental soil P risk indicator in the region) under a corn–soybean rotation in a clay loam soil of the Lake Erie Basin, southwestern Ontario, Canada, from 2008 to 2018. Corn and soybean grain yields with PDD were identical to those with continuous P addition (CPA), averaged at 7.7 Mg ha–1 for corn and 3.7 Mg ha–1 for soybean, over 11 years. Similarly, no significant differences in crop P uptake and removal were found between PDD and CPA. Compared to CPA, PDD increased net farming income by Canadian dollar (CAD) 104–125 ha–1 year–1 (i.e., USD 78.5–94.4 ha–1 year–1), with savings on P fertilizer materials and associated application costs. Soil P loss risks with PDD reduced, as indicated by soil test P that, in the top layer (0–15 cm), decreased linearly with crop production year at 3.27 mg P kg–1 year–1 or 16.2 mg P kg–1 per 100 kg crop P removal per hectare, while in the lower soil layers, 15–90 cm, it remained unchanged. In comparison, CPA of 50 kg P ha–1 sustained soil test P in the entire soil profile, 0–90 cm, over the 11-year period. PDD can be a beneficial management practice utilizing legacy P in soils to achieve both agronomic and economic goals in an environmentally sustainable manner.